Understanding change and continuity in walking and cycling over the life course: A first look at gender and cohort differences. - Jones, Heather; Chatterjee, Kiron; Gray, Selena (Springer VS, 2015)
Research of walking and cycling is dominated by approaches oriented to explanations of behavioural outcomes as a function of contemporaneous circumstances. The lack of a long term temporal perspective precludes understanding of behaviour as an outcome of past behaviour and experiences, and impedes our ability to support walking and cycling as life-long practices. This essay presents a study that was conducted at the nexus of health and travel behaviour research to gain a life course perspective of walking and cycling. Individual's retrospective reasoning of change and continuity in their behaviour through life events and transitions was captured using biographical interviews. Biographies of older and younger adults indicated that behaviour developments were associated with changes in location, mobility resources, roles and health status and highlighted that the potential for adaptive, restorative and diminishing changes.
Keywords: Individualverkehr; Mobilität; Verkehrsmittelwahl; Fahrradverkehr; Fußgängerverkehr; Geschlecht; Lebensalter; Verkehrsforschung; Alltagsmobilität; Biographie